Consumer Behavior Analysis in the Age of Big Data for Effective Marketing Strategies - Williams, John (International Journal of Strategic Marketing Practice, 2024)
Purpose: The aim of the study was to examine the consumer behavior analysis in the age of big data for effective marketing strategies. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found that consumer behavior analysis in the age of big data presents a transformative opportunity for businesses to enhance their marketing strategies and better understand their target audiences. The studies discussed demonstrate the effectiveness of leveraging Big Data analytics in various domains such as social media sentiment analysis, personalized marketing, predictive analytics, customer segmentation, location-based marketing, and real-time personalization. These strategies enable businesses to tailor their marketing efforts more precisely, leading to increased consumer interest, improved engagement, and higher conversion rates. Unique Contribution to Theory, Practice and Policy: Social Identity Theory, Information Processing Theory & Technology Acceptance Model (TAM) may be used to anchor future studies on Consumer Behavior Analysis in the Age of Big Data for Effective Marketing Strategies. Promote the adoption of advanced data analytics tools and techniques by businesses to enhance their marketing strategies. Companies should invest in robust data infrastructure, analytics platforms, and talent to effectively collect, analyze, and interpret consumer data. By leveraging predictive analytics, sentiment analysis, customer segmentation, and real-time personalization, businesses can tailor their marketing efforts to individual consumer preferences and behaviors, leading to improved engagement, customer satisfaction, and ultimately, increased sales and profitability. Advocate for the development of regulatory frameworks that balance consumer privacy rights with the benefits of data-driven marketing. Policymakers should collaborate with industry stakeholders to establish guidelines and standards for ethical data collection, usage, and storage.